SUPRA-SUBDUCTION ZONE PYROXENITES FROM SAN JORGE AND SANTA ISABEL (SOLOMON ISLANDS) - Berly T.J.; Hermann J.; Arculus R.J.; Lapierre H. (My University, 2006)
Peridotites associated with pyroxenites (with rare olivine and spinel) are exposed on the islands of San Jorge and Santa Isabel in the Solomon Islands. Orthopyroxenite occurs in large outcrops (?100?m2) whereas websterite and clinopyroxenite occur as layers and veins/dykes in peridotites. The bulk compositions of the pyroxenites are characterized by high Mg2+/(Mg2+ + Fe2+) (0·78–0·91) and low Al2O3 (<2·7 wt %). Low rare earth element abundances are coupled with large ion lithophile element enrichments and positive Sr and Pb anomalies (primitive mantle-normalized) relative to adjacent rare earths. Temperatures of equilibration for the pyroxenites are between 950 and 1050°C. These relatively low temperatures, combined with the occurrence of primary fluid inclusions, suggest that the pyroxenites formed by interaction of peridotite protoliths with an aqueous fluid. Bulk-rock and mineral compositions of the orthopyroxenites are similar to those of mantle-derived pyroxenites, whereas the websterites have closer chemical affinity with crustal arc cumulates. Nevertheless, field relationships plus petrological, textural and geochemical evidence are consistent with formation of all pyroxenite types in supra-subduction zone mantle, resulting from metasomatism of peridotite by subducted Pacific Plate-derived fluid. Such a setting for pyroxenite has not previously been reported in detail. We propose that these processes produce mantle pyroxenite with compositions similar to crustal pyroxenite.
Keywords: mantle metasomatism; pyroxenite; supra-subduction zone